maxkay47 wrote:

Hey Guys,

as I have found this forum today I would like to share my thoughts on the GMAT with you. I´ve began preparing for the test about a week ago and right now I´m still fighting easy problems.

I got a qestion that needs two equations two be created. I got the first equation, which is:

\sqrt{3-2x} = \sqrt{2x}+1

When I square both sides, I do get

3-2x = ?

My problem is that I don´t know any rule that leads to the correct term on the right side, which Is (as indicated in the explanations)

3-2x = 2x+2*\sqrt{2x}+1

Anyone any idea how this works?

Maybe some of you can help me with this.

Thanks in advance

Max

3 - 2x =( \sqrt{2x} + 1) * ( \sqrt{2x} + 1)

= 2x + \sqrt{2x} + \sqrt{2x} + 1

= 2x + 2 \sqrt{2x} + 1

_________________

Blog: The MBA Journey of an African Doctor

Blog updated: July 27, 2014